2017
DOI: 10.1007/s12178-017-9438-z
|View full text |Cite
|
Sign up to set email alerts
|

Management of Complex Anterior Shoulder Instability: a Case-Based Approach

Abstract: Arthroscopic Bankart repair is well documented for having successful outcomes in patients with isolated labral tear involvement with minimal bone loss. Latarjet is a generally accepted procedure in patients with 20-30% glenoid bone loss. When bone loss exceeds that which cannot be managed through Latarjet, a range of options exist and are highly dependent upon the extent of osseous deficiency on both the glenoid and humeral sides, surgeon experience, and patient-specific factors. The use of reverse total shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Even with arthroscopic or open reduction, these cases have historically been associated with poor range of motion and pain outcomes postoperatively [29][30][31][32] . Several studies have reported positive outcomes with rTSA in the management of chronic locked shoulder dislocation, including both anterior and posterior dislocations [9,24,27,28,30,[32][33][34] . Reverse TSA has an added benefit in these patients as many will have concomitant rotator cuff disruption from traumatic primary or recurring dislocations, making them unlikely to benefit from standard TSA or other more conservative treatments [2,5,23,25,35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with arthroscopic or open reduction, these cases have historically been associated with poor range of motion and pain outcomes postoperatively [29][30][31][32] . Several studies have reported positive outcomes with rTSA in the management of chronic locked shoulder dislocation, including both anterior and posterior dislocations [9,24,27,28,30,[32][33][34] . Reverse TSA has an added benefit in these patients as many will have concomitant rotator cuff disruption from traumatic primary or recurring dislocations, making them unlikely to benefit from standard TSA or other more conservative treatments [2,5,23,25,35] .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have found the use of rTSA as a primary treatment for proximal humerus fractures is associated with significantly higher measures function, lower rates of complications, and less need for further revision when compared to other surgical treatment plans like ORIF or hemiarthroplasty, even when those are later revised with rTSA [33,[40][41][42][43] . While there are several studies already cited above that examine the role of rTSA in chronic locked shoulder dislocation, very few have explored the use of rTSA as a primary treatment for this condition [9,33,34] . In agreement with the findings of those studies, the authors support the use of rTSA as a primary surgical treatment for chronic locked glenohumeral dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder instability encompasses a wide spectrum from subluxation to frank dislocation with a high prevalence affecting mainly the young, active population with a significant impact on the quality of life [1,2]. With an incidence of 23.9/100,000 person-years, anterior shoulder instability is a common problem [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although no large cohorts are available in the literature, several small case series report their outcomes for HA, ATSA, and/or RTSA in the setting of chronic glenohumeral dislocation. 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Compiling the results of these studies can provide surgeons with a single source of streamlined information and help to identify factors that affect outcomes. The aim of this systematic review was to summarize the literature that has examined clinical outcomes and predictors of clinical outcomes for chronic glenohumeral dislocations treated with arthroplasty.…”
mentioning
confidence: 99%